Modelling Fallschirmjäger Figures 'Say "Cheese"!' Fallschirmjäger Italy, 1943 : In 54mm scale /: In 54mm scale. (2012 copyright 2012) - Forns, Jaume Ortiz; Romero, Daniel Alfonsea
No abstract available